2018
DOI: 10.1016/j.chom.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Response to Fungal Dysbiosis by Gut-Resident CX3CR1+ Mononuclear Phagocytes Aggravates Allergic Airway Disease

Abstract: Summary Sensing of the gut microbiota, including fungi, regulates mucosal immunity. Whether fungal sensing in the gut can influence immunity at other body sites is unknown. Here we show that fluconazole-induced gut fungal dysbiosis has persistent effects on allergic airway disease in a house dust mite challenge model. Mice with a defined community of bacteria, but lacking intestinal fungi were not susceptible to fluconazole-induced dysbiosis, while colonization with a fungal mixture recapitulated the detriment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 34 publications
(66 reference statements)
4
104
0
1
Order By: Relevance
“…27 The destruction of lung immunity by antifungal agents such as uconazole aggravated allergic airway disease in model mice when it reduced gut fungi. 28 These results are consistent with our ndings showing that most depleted gut fungi are positively correlated with a reduction in blood lymphocytes. On the other hand, symbiotic gut fungi can protect local and systemic immunity by providing complementary microbial stimulation in place of stimulation by bacteria.…”
Section: Discussionsupporting
confidence: 93%
“…27 The destruction of lung immunity by antifungal agents such as uconazole aggravated allergic airway disease in model mice when it reduced gut fungi. 28 These results are consistent with our ndings showing that most depleted gut fungi are positively correlated with a reduction in blood lymphocytes. On the other hand, symbiotic gut fungi can protect local and systemic immunity by providing complementary microbial stimulation in place of stimulation by bacteria.…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, there is increasing evidences showing the influence of gut mycobiota on extragastrointestinal organs immune responses. A typical example is through a study by [82]. Overall, these studies revealed a clear link between gut mycobiota, pulmonary immune responses, and lung diseases, which further consolidate the idea of the existence of mycobiota-gut-lung axis.…”
Section: Mediators Of Inflammationmentioning
confidence: 62%
“…In addition to antibiotic treatment, antifungal treatment induces changes to both the bacterial and fungal communities in the gut of specific pathogen-free (SPF) mice and has been shown to exacerbate type 2 allergic airway inflammation and eosinophilia in a HDM model of AAD (Wheeler et al, 2016;Li et al, 2018). Continuous supplementation with three fungal species identified in this model to be overrepresented in the gut following antifungal treatment (Aspergillus amstelodami, Wallemia mellicola [sebi], and Epicoccum nigrum) (Wheeler et al, 2016;Li et al, 2018) or with Wallemia mellicola alone following antibiotic treatment (Skalski et al, 2018) similarly increases asthma severity (Figure 3) (Wheeler et al, 2016;Skalski et al, 2018). Antifungal treatment and the introduction of dysbiotic fungal communities to SPF mice in these studies results in changes to gut bacterial communities, including depletions of bacteria from the Lactobacillaceae family Skalski et al, 2018).…”
Section: Looking Beyond Bacteria: Fungi: the Forgottenmentioning
confidence: 99%
“…However, the AAD-exacerbating effects of supplementation with a dysbiotic fungal community can be recapitulated in altered Schaedler flora mice without pre-treatment with antibiotics and in the absence of substantial changes to the bacterial microbiota Skalski et al, 2018). Furthermore, Li et al (2018) recently demonstrated that direct sensing of antifungal-induced fungal dysbiosis by gut-resident CX3CR1 + mononuclear phagocytes increases numbers of Th2 cells in the lamina propria and is responsible for fungal dysbiosis-associated increased airway inflammation in a HDM model of AAD, independent of antifungal-associated changes to the bacterial communities . Thus, in addition to having potential indirect effects on airway inflammation via restructuring of immunomodulatory gut bacterial populations or the production of systemic Immunity 52, February 18, 2020 247 Immunity Review metabolites, asthma-associated fungal dysbiosis in the gut can have direct effects on host innate and adaptive immune cell populations.…”
Section: Looking Beyond Bacteria: Fungi: the Forgottenmentioning
confidence: 99%